2008
DOI: 10.2527/jas.2007-0217
|View full text |Cite
|
Sign up to set email alerts
|

Constitution and evaluation of a long-lived productive rabbit line1

Abstract: An evaluation of a new maternal line (LP) of rabbits was carried out. This new line was founded following a scheme similar to that applied in the selection for hyperprolificacy in rabbits or pigs. In this case, the selection criteria were hyperlongevity and an independent culling level near the average for prolificacy. Evaluation was carried out by comparison of the reproductive and longevity performance of the LP line with another maternal line recognized for good reproductive performance and standard longevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 20 publications
6
67
0
1
Order By: Relevance
“…However, the V does produced significantly larger litters at third partum (+1.88 kits total born and +1.20 kits born alive) in unconstrained conditions (NC). These values are in agreement with a large-scale study (>200 does per line; Sánchez et al, 2008) that reported higher total born (+0.74 kits), born alive (+0.77 kits) and weaned kits (+0.54) during the first three partum for V does as compared with LP does. The main differences between LP and V does in the NC environment were observed in the evolution of DE intake, milk yield and PFT.…”
Section: Genetic Differences In Nc Environmentsupporting
confidence: 91%
See 4 more Smart Citations
“…However, the V does produced significantly larger litters at third partum (+1.88 kits total born and +1.20 kits born alive) in unconstrained conditions (NC). These values are in agreement with a large-scale study (>200 does per line; Sánchez et al, 2008) that reported higher total born (+0.74 kits), born alive (+0.77 kits) and weaned kits (+0.54) during the first three partum for V does as compared with LP does. The main differences between LP and V does in the NC environment were observed in the evolution of DE intake, milk yield and PFT.…”
Section: Genetic Differences In Nc Environmentsupporting
confidence: 91%
“…A total of 164 rabbit females started the trial, 85 from line LP and 79 from line V. The LP line was founded on reproductive longevity criteria by selecting females from commercial farms (indistinctively of its origin; i.e. purebreed or crossbreed of synthetic lines) that had a minimum of 25 partum with more than 7.5 kits born alive per partum (more details of the LP line constitution are given in Sánchez et al, 2008) and then selected by litter size at weaning for the subsequent six generations. Line V was constituted from four specialised maternal lines into a composite synthetic line and then selected by litter size at weaning (Estany et al, 1989) for 36 generations.…”
Section: Animalsmentioning
confidence: 99%
See 3 more Smart Citations